Criminal and Other Sanctions and Measures Under EU Directive (2024/1203) on the Protection of the Environment Through Criminal Law - Lukić, Natalija (Glasnik Advokatske komore Vojvodine, 2026)
The paper analyses certain provisions of EU Directive 2024/1203 on the criminal law protection of the environment, focusing on criminal and other sanctions and measures. Unlike the previous Directive 2008/99/EC, which merely stated that criminal sanctions should be effective, proportionate, and dissuasive, the new Directive regulates this matter in greater detail. In the first part of the paper, the author highlights the most important innovations introduced by the new Directive and provides an overview of criminal and other sanctions and measures applicable to natural and legal persons. The second part of the paper addresses the issue of the effectiveness of criminal sanctions in relation to environmental crime, with special attention given to the advantages and disadvantages of criminal sanctions imposed on legal entities. The third part offers a discussion on the potential significance of Directive 2024/1203 for Serbian criminal legislation.